Quality improvement of Three-Way Catalytic Converter (TWC) design by using Failure Modes and Effects Analysis (FMEA) - Syed Najib Syed Abdul Bahari
This research presents the application of FMEA method on Three-Way Catalytic Converter (TWC) system. Catalytic converter of auto-exhaust emission is one of the most successful applications of heterogeneous catalysis, both in commercial and environmental point of view. Catalytic converter has been proved critical to controlling pollution of CO-HC-NOx caused by automobile sources. TWC system functional lifetime is affected due to catalysts deactivation causes. Latest legislation required carmakers to produced longer lifetime for TWC system. This research is conducted by using Failure Modes and Effects Analysis (FMEA) method. This method is used on Three-Way Catalytic Converter (TWC) system and design to determine and ranks its potential deactivation factors. FMEA method is a systematic and analytical quality planning tool for identifying and addressing what potentially could go wrong with a product or process. It is widely accepted that FMEA is one of the best quality improvement tool. For the last several decades, FMEA has been widely used in industry especially in automotive sectors. It is expected to enhance the lifetime of the TWC by improving its resistance to deactivation. This aim will be achieved by providing/suggesting recommendation action 'plan to the TWC system to improve its quality via lowering the exhaust emission. One of practical contributions of this research is to provide guidelines to quality engineer in monitoring the efficiency of TWC system from the FMEA report. This research will be covering on the system and design of the TWC itself as the most important part for controlling the exhaust emission from automobiles. The model used in this study is a Spark Ignition (SI) gasoline engine. Improving its resistance to deactivation will contribute to longer lifetime of automotive catalytic converter.